Yak Pericardium as an Alternative Biomaterial for Transcatheter Heart Valves - Song, Mingzhe; Tang, Zhenjie; Liu, Yuhong; Xie, Xinlong; Qi, Xiaoke; Wu, Qiying; Jiang, Zhenlin; Wu, Zhongshi; Qian, Tao (Frontiers in Bioengineering and Biotechnology, 2021)
Transcatheter aortic valve implantation (TAVI) has received much attention and development in the past decade due to its lower risk of complication and infections compared to a traditional open thoracotomy. However, the current commercial transcatheter heart valve does not fully meet clinical needs; therefore, new biological materials must be found in order to meet these requirements. We have discovered a new type of biological material, the yak pericardium. This current research studied its extracellular matrix structure, composition, mechanical properties, and amino acid content. Folding experiment was carried out to analyze the structure and mechanics after folding. We also conducted a subcutaneous embedding experiment to analyze the inflammatory response and calcification after implantation. Australian bovine pericardium, local bovine pericardium, and porcine pericardium were used as controls. The overall structure of the yak pericardium is flat, the collagen runs regularly, it has superior mechanical properties, and the average thickness is significantly lower than that of the Australian bovine and the local bovine pericardium control groups. The yak pericardium has a higher content of elastic fibers, showing that it has a better compression resistance effect during the folding experiment as well as having less expression of transplantation-related antigens. We conducted in vivo experiments and found that the yak pericardium has less inflammation and a lower degree of calcification. In summary, the yak pericardium, which is thin and strong, has lower immunogenicity and outstanding anti-calcification effects may be an excellent candidate valve leaflet material for TAVI.